2023
DOI: 10.1021/acsenergylett.3c00262
|View full text |Cite
|
Sign up to set email alerts
|

Nanographene Coupled with Interfacial Pyrene Derivatives for Thermally Stable Perovskite Solar Cells

Abstract: Although high-efficiency perovskite solar cells (PSCs) have been achieved using a hole-extracting material, spiro-MeOTAD, thermal stability has been unattainable due to the low glass transition temperature of spiro-MeOTAD and additives therein. Here, we report on the use of nanographene-based hole-transporting materials coupled with a pyrene derivative as an interface modifier for thermally stable and high efficiency PSCs. Asymmetric methyl and methoxy groups are introduced in the diphenyl­amino group that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Significant efforts are being made to improve long-term stability in PSCs. The initial effort was to introduce alloying of A-site cations and halide ions in 3D perovskites. Surface treatments have been widely employed to passivate surface defects and achieve long-term stability. , Another approach involves depositing a 2D perovskite phase on top of the 3D perovskite phase thus creating a 2D/3D architecture for solar cell operation. ,, ,, In a 2D/3D architecture of perovskite solar cells, the 3D perovskite phase is responsible for efficient photon conversion, while the 2D perovskite phase provides stability against moisture due to the hydrophobic spacer cations. This architecture has been shown to improve the long-term stability of PSCs at room temperature, and in some cases, even to improve the photon conversion efficiency. ,, ,,,,, However, studies from several groups, as well as ours, have recently shown the dynamic nature of the 2D/3D interface, as it becomes unstable under thermal stress or light soaking. ,, The 2D/3D interface undergoes a transformation because of slow cation exchange, thus replacing the sharp 2D/3D interface with a gradient structure of 2D phases (n = 1, 2, 3, ...). , The cation exchange rate depends on the cation (both A-site and spacer cations), with alkylammonium ions such as butylammonium showing greater mobility under thermal and light stress compared to other more bulky spacer cations. , It has been shown that at elevated temperatures, for example at 50 °C, the deterioration of the 2D/3D interface results in the efficiency loss of perovskite solar cells . A r...…”
mentioning
confidence: 99%
“…Significant efforts are being made to improve long-term stability in PSCs. The initial effort was to introduce alloying of A-site cations and halide ions in 3D perovskites. Surface treatments have been widely employed to passivate surface defects and achieve long-term stability. , Another approach involves depositing a 2D perovskite phase on top of the 3D perovskite phase thus creating a 2D/3D architecture for solar cell operation. ,, ,, In a 2D/3D architecture of perovskite solar cells, the 3D perovskite phase is responsible for efficient photon conversion, while the 2D perovskite phase provides stability against moisture due to the hydrophobic spacer cations. This architecture has been shown to improve the long-term stability of PSCs at room temperature, and in some cases, even to improve the photon conversion efficiency. ,, ,,,,, However, studies from several groups, as well as ours, have recently shown the dynamic nature of the 2D/3D interface, as it becomes unstable under thermal stress or light soaking. ,, The 2D/3D interface undergoes a transformation because of slow cation exchange, thus replacing the sharp 2D/3D interface with a gradient structure of 2D phases (n = 1, 2, 3, ...). , The cation exchange rate depends on the cation (both A-site and spacer cations), with alkylammonium ions such as butylammonium showing greater mobility under thermal and light stress compared to other more bulky spacer cations. , It has been shown that at elevated temperatures, for example at 50 °C, the deterioration of the 2D/3D interface results in the efficiency loss of perovskite solar cells . A r...…”
mentioning
confidence: 99%
“…Carbon nanomaterials (Yan et al, 2023) have attracted worldwide attention since they have demonstrated great potential in energy storage (Fu et al, 2023;Gadipelli et al, 2023;Gao et al, 2023;Mo et al, 2023;Senokos et al, 2023) and conversion (Zhang et al, 2022;Kim et al, 2023;Lv et al, 2023;Peng et al, 2023) to relieve the environmental problem and energy crisis (Gao et al, 2022;Marangon et al, 2023;Yan et al, 2023). Carbon nanomaterials also play a significant role in the field of electrocatalysis of ORR due to their low cost, high performance and excellent stability (Zaman et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Typically, high-performance PSC devices require the assistance of excellent hole transport materials (HTMs) with suitable energy levels, high hole mobility and conductivity to achieve efficient hole extraction and transport. [7][8][9][10][11][12][13] To date, 2,2 0 ,7,7 0 -tetrakis (N,N-di-pmethoxyphenylamine)-9,9 0 -spirobifluorene (Spiro-OMeTAD) is a state-of-art HTM that enables PSCs to achieve superior efficiency. [14][15][16][17][18][19][20][21] However, the complex synthesis process of Spiro-OMeTAD leads to a significant increase of the total cost of PSCs, limiting its future largescale industrial applications.…”
Section: Introductionmentioning
confidence: 99%